2018
DOI: 10.1371/journal.pone.0191019
|View full text |Cite
|
Sign up to set email alerts
|

Capillary networks and follicular marginal zones in human spleens. Three-dimensional models based on immunostained serial sections

Abstract: We have reconstructed small parts of capillary networks in the human splenic white pulp using serial sections immunostained for CD34 alone or for CD34 and CD271. The three-dimensional (3D) models show three types of interconnected networks: a network with very few long capillaries inside the white pulp originating from central arteries, a denser network surrounding follicles plus periarterial T-cell regions and a network in the red pulp. Capillaries of the perifollicular network and the red pulp network have o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…A paraffin-embedded sample of a normal human spleen which had been studied previously 23 and which was found representative of the majority of adult human spleens with small symmetric secondary follicles was processed to 24 serial sections which were simultaneously stained for CD34 and SMA in brown colour and for CD271 in blue (Fig. 1a,c,e ).…”
Section: Resultsmentioning
confidence: 99%
“…A paraffin-embedded sample of a normal human spleen which had been studied previously 23 and which was found representative of the majority of adult human spleens with small symmetric secondary follicles was processed to 24 serial sections which were simultaneously stained for CD34 and SMA in brown colour and for CD271 in blue (Fig. 1a,c,e ).…”
Section: Resultsmentioning
confidence: 99%
“…28 It was also suggested that the specialized stromal marginal reticular cells form a barrier inside the MZ, which guarantees the maintenance of gradients necessary for positioning of migratory B and T cells in the WP. 30 In addition to cell adhesion molecules, the α-SMApositive reticular framework expresses the chemokines CCL21, CXCL12 and CXCL13 in the human spleen. 28,31 In the ontogeny of the human fetal spleen, α-SMA-positive stromal cells were demonstrated to express CCL21 and CXCL13, and induce the colonization of B and T lymphocytes into the WP.…”
Section: Discussionmentioning
confidence: 99%
“…a. Healing in general We routinely use our opticalflow-based interpolation [67] to reduce the anisotropy of the data in our reconstructions [99,101]. Having initially acquired the data with spatial resolution of 0.5 µm/voxel × 0.5 µm/voxel × 7 µm/voxel, we produce volumes with 0.5 µm/voxel × 0.5 µm/voxel × 1 µm/voxel for the actual 3D reconstruction.…”
Section: Healing Of Separate Channelsmentioning
confidence: 99%
“…In practice, the final meshes were visualized in our virtual-reality-based application [66]. With the ability to place annotations and perform mesh painting, our software is used by the domain experts for knowledge discovery [99][100][101]. Fig.…”
Section: Further Processing and Visualizationmentioning
confidence: 99%
See 1 more Smart Citation